Tradisi Cuci Pusaka Pada malam Satu Suro dan Gaman Bekerja di Desa Tanjung, Blimbing, Sambirejo Sragen: The tradition of washing heritage on the night of one suro and gaman work in tanjung village, blimbing - Anita Putri Lestari, Anita (Rihlah : Jurnal Sejarah dan Kebudayaan, 2022)
This study seeks to describe the tradition of ngumbah gaman. The purpose of this study is to describe the history, meaning, function, and also some of the impacts of the ngumbah gaman tradition which is still preserved today in Tanjung Village, Sambirejo District, Sragen Regency. The method used in this research is descriptive-qualitative, that is, it examines a phenomenon of the ngumbah gaman tradition. Data collection techniques in the research conducted were observation and interviews using note-taking techniques. The results of this study are the history of the nunmbah gaman which has existed since ancient times, the meaning of the ngumbah gaman tradition, namely as one of giving thanks to God for the life that has been given, as well as several conditions that must be carried out in carrying out the ngumbah gaman tradition, then the impact from the tradition of ngumbah gaman.